Parameters of cardiac symptoms in young athletes using the Heartbytes database - Jones, J. C.; Sugimoto, D.; Kobelski, G. P.; Rao, P.; Miller, S.; Koilor, C.; Corrado, G. D.; Shipon, D. M. (The Physician and Sportsmedicine, 2020)
Introduction: To determine clinical parameters that are related to abnormal cardiac symptoms in physically active youth.